AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN WRITING RECOUNT TEXT AT TENTH GRADE OF SMA NEGERI 7 MEDAN - Diane Sarima Lestari Simbolon; Nurhayati Sitorus; Sahat Taruli Siahaan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to identify the difficulties faced by tenth-grade students in writing recount texts and to analyze the factors causing those difficulties. This research employed a qualitative descriptive method. The subjects of this study were tenth-grade students of SMA Negeri 7 Medan. The data were collected through writing tests and interviews. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that students experienced both linguistic and non-linguistic difficulties in writing recount texts. The linguistic difficulties included limited vocabulary, difficulties in using grammar (especially past tense), problems in organizing ideas, and difficulties in expressing ideas in written form. Meanwhile, the non-linguistic factors included lack of motivation and interest, low self-confidence, limited time allocation, lack of writing practice, lack of experience in writing personal events, and insufficient understanding of the teacher’s explanation. Among those factors, vocabulary limitation and grammar (past tense) were the most dominant difficulties experienced by the students. These findings indicate that students need more practice, vocabulary enrichment, grammar reinforcement, and motivational support to improve their ability in writing recount texts.